Is telehealth effective in managing malnutrition in community-dwelling older adults? A systematic review and meta-analysis. (May 2018) - Marx, Wolfgang; Kelly, Jaimon T.; Crichton, Megan; Craven, Dana; Collins, Jorja; Mackay, Hannah; Isenring, Elizabeth; Marshall, Skye
Highlights: Malnutrition-focused telephone consultations for older adults appear feasible. Telehealth interventions can improve quality of life for malnourished older adults. Telehealth can improve protein intake by 0.13 g/kg in malnourished older adults. Compared with usual care, malnutrition-focused telehealth appears cost-effective. Larger well designed randomised controlled trials are needed to strengthen evidence. Abstract: Telehealth offers a feasible method to provide nutrition support to malnourished older adults. This systematic review and meta-analysis aims to determine the efficacy of telehealth methods in delivering malnutrition-related interventions to community-dwelling older adults. Studies in any language were searched in five electronic databases from inception to 2nd November 2017. Quality of the evidence was assessed using the Cochrane Risk of Bias tool and the GRADE approach. Nine studies were identified, with results published across 13 included publications, which had mostly low to unclear risk of bias. There were two interventions delivered to disease-specific groups, one with kidney disease and one with cancer; the remaining seven interventions were delivered to patients with mixed morbidities following discharge from an inpatient facility. Seven studies delivered telehealth via telephone consultations and two used internet-enabled telemedicine devices. Ten meta-analyses were performed. Malnutrition-focused telehealth interventions were found to improve protein intake in older adults by 0.13 g/kg body weight per day ([95%CI: 0.01–0.25]; P = .03; n = 2 studies; n = 200 participants; I 2  = 41%; GRADE level: low) and to improve quality of life (standardised mean difference: 0.55 [95%CI: 0.11–0.99]; P = .01; n = 4 studies with n = 9 quality-of-life tools; n = 248 participants; I 2  = 84%: GRADE level: very low). There were also trends towards improved nutrition status, physical function, energy intake, hospital readmission rates and mortality in the intervention groups. Overall, this review found telehealth is an effective method to deliver malnutrition-related interventions to older adults living at home, and is likely to result in clinical improvements compared with usual care or no intervention. However, further research with larger samples and stronger study designs are required to strengthen the body of evidence.